The sample size to consider in a study of the functional magnetic resonance imaging (fMRI) using a 1.5 Tesla magnetic resonator [Tamaño de muestra a considerarse en un estudio de resonancia magnética funcional (RMF) con un equipo de resonancia magnéticade 1.5 T] - Aguirre Reyes, D. (2012)
This work presents an analysis of the necessary tools and special considerations to develop investigation in brain using fMRI with a magnetic resonator of 1.5 T field. This work presents the sample size and the necessary task time to use for showing results.